On Boredom : Essays in art and writing - Holmboe, Rye Dag; Morris, Susan (UCL Press, 2021)
What do we mean when we say that we are bored? Or when we find a subject boring? Contributors to On Boredom: Essays in art and writing, which include artists, art historians, psychoanalysts and a novelist, examine boredom in its manifold and uncertain reality. Each part of the book takes up a crucial moment in the history of boredom and presents it in a new light, taking the reader from the trials of the consulting room to the experience of hysteria in the nineteenth century. The book pays particular attention to boredom's relationship with the sudden and rapid advances in technology that have occurred in recent decades, specifically technologies of communication, surveillance and automation. On Boredom is idiosyncratic for its combination of image and text, and the artworks included in its pages - by Mathew Hale, Martin Creed and Susan Morris - help turn this volume into a material expression of boredom itself. With other contributions from Josh Cohen, Briony Fer, Anouchka Grose, Rye Dag Holmboe, Margaret Iversen, Tom McCarthy and Michael Newman, the book will appeal to readers in the fields of art history, literature, cultural studies and visual culture, from undergraduate students to professional artists working in new media.